Ultraestructura del bambú Guadua paniculata (Poaceae: Bambusoideae) de Costa Rica - Montiel, Mayra (Universidad de Costa Rica, 2006)
Sections of leaf lamina, leaf sheath and branches of adult Guadua paniculata collected in Costa Rica, were studied ultrastructurally. Diagnostic ultrastructural characteristics include the cellular pattern of the adaxial zone in the leaf blade; the large unicellular trichomes of the abaxial area, the more numerous auricular trichomes, grouped in number of 17, the pattern of cuticular wax and the bands of stomata surrounded by ceric papillae. Rev. Biol. Trop. 54(Suppl. 2): 29-34. Epub 2006 Dec. 01.